PENGEMBANGAN KAPASITAS KELOMPOK TANI HUTAN KIBUK DALAM TATA KELOLA PERHUTANAN SOSIAL YANG BAIK (GOOD FOREST GOVERNANCE) DI KOTA PAGARALAM - Agus; Purnama, Dadang Hikmah; Sartika, Diana Dewi (Politeknik Negeri Jakarta, 2024)
The Kibuk forest farmer group has been managing Kibuk social forestry for seven years. Capacity building initiatives implemented by the Dempo Region X Forest Management Unit and Hutan Kita Institute have not yet fully enhanced the efficacy of the individual and institutional capacity of the Kibuk forest farmer group, thereby impeding the capacity of the forest farmer group to fulfill its role and function in social forestry governance. This research employs a qualitative verification methodology with a case study strategy. The informants were comprised of individuals engaged in capacity building initiatives and the communities that benefited from these efforts. The findings of this study indicate that the capacity-building initiatives for the Kibuk forest farmer group have not yet fully improved the individual capacity of farmers. While there has been an increase in expertise in non-agricultural fields, knowledge of good social forestry governance and resources, and an improvement in the group's ability to engage in social forestry activities, there are still significant challenges in terms of institutional capacity. These include the lack of a complete social forestry business group structure and a lack of ideas regarding the development of social forestry areas. Members of the Kibuk forest farmer group have not yet been able to assume their own responsibilities. The Kibuk forest farmer group has not yet mastered management and has not yet been able to realize transparency and accountability. The institutional capacity development process of the Kibuk forest farmer group still ignores actual needs assessment, not all action plans and strategies can be implemented, program implementation is limited, monitoring and evaluation are not carried out credibly. The pattern of capacity building remains constrained to the subordinate union of partnership and passive participation of members, and has not yet encompassed a comprehensive and integrated approach. It is necessary to develop an institutional capacity-building model that can enhance the role and function of the Kibuk forest farmer group in implementing social forestry governance principles in an effective manner.